L2 acquisition of Wh-interrogatives at the syntax-discourse interface: interface hypothesis again [version 1; peer review: 2 approved] - Shormani, Mohammed (F1000 research, 2023)
This study sets out to answer one major question: do linguistic phenomena relating to syntax-discourse interface constitute difficulty for Yemeni learners of English? It presents data from an experiment on the acquisition of L2 English wh-interrogatives by L1 Yemeni Arabic speakers, aiming to provide empirical evidence either in support of the Interface Hypothesis (IH) or against it. Two learner groups, intermediate and advanced, were recruited as participants of the study, and a native speaker group of (British) English was also recruited as the control group. The advanced group learners have a near-native proficiency in English. The data utilized consisted of 20 (D-)iscourse linked and non-d-linked wh-interrogatives presented to the three groups in the form of a (decontextualized) bi-modal multiple-choice paced judgement task. Results showed that both learner groups, specifically the advanced learners, performed near-native like in the non-d-linked, but far short of near/native-like performance in the d-linked wh-interrogatives. The study concluded that L2 learners' English is still vulnerable at the syntax-discourse interface, hence supporting the IH.